The Impact of Mortality Salience on Purchase Intention and Creativity Evaluation on Products During COVID-19 Pandemic - Zu, Chong; Zhou, Xiang; Cui, Yu-Xin; Liu, Yan-Fang; Hu, Yue-Xin; Li, Dong-Qi; Zeng, Hui (Frontiers in Psychology, 2021)
In the environment of COVID-19, people are faced with mortality salience (MS) and socioeconomic crisis. According to the terror management theory, the MS would lead to particular consumption attitudes and behaviors caused by the self-esteem and cultural worldview defense. The creativity as a potential value of products needs to be examined to explore how the MS changed the creativity evaluation of three types of products categorized into normal, renovative, and innovative products, based on the degree of originality (Zhang et al., 2019). Two experiments were conducted to examine (1) the MS effect on the creativity and purchase intention evaluation and (2) both MS and country-of-origin effect on the evaluations. The results show that usefulness and purchase intention are affected by both effects, and the novelty is mainly affected by MS.